Performance optimization of a microwave-coupled plasma-based ultralow-energy ECR ion source for silicon nanostructuring - Joy Mukherjee; Safiul Alam Mollick; Tanmoy Basu; Tapobrata Som (Beilstein Journal of Nanotechnology)
This paper presents a comprehensive optimization of key parameters for generating ion beams in a microwave-coupled plasma-based ultralow-energy electron cyclotron resonance ion source, generally used for nanostructuring solid surfaces. The investigation focuses on developing, accelerating, and extracting Ar ions from a magnetron-coupled plasma cup utilizing a three-grid ion extraction composed of molybdenum. The study systematically examines the dependence of ion beam current on critical parameters, such as gas pressure, magnetron power, extraction voltage, and ion energies. The Gaussian nature of the beam profile is scrutinized and elucidated within the context of grid extraction-based ion sources. Plasma physics principles are employed to interpret the observed variations in the beam current with various parameters. The optimized beam current is used to investigate the inert ion-induced nanopatterning of silicon surfaces, at various ion fluences and incidence angles. The pre- and post-bombardment changes in optical properties, resulting from nanopatterned surfaces, are investigated using UV–vis reflectivity measurements and correlated with the dimensions of the nanopatterns. This manuscript highlights the potential applications arising from these findings, emphasizing the transformative impact of nanopatterning through low-energy inert ions.